A astrologia em Portugal no século XVI: o caso do astrólogo cristão-novo Manuel Rodrigues no Tribunal do Santo Ofício da Inquisição - Pereira, Taylana Lis de Araújo (2021)
There is a growing number of studies and works on the importance and contribution of sephardic Jews and new christians, their descendants, in the propagation of mystical and esoteric practices in the Iberian Peninsula during the Middle and Modern Ages (especially in the 16th and 17th centuries). Influenced by the second chapter of the jewish mystical tradition, known as Kabbalah, developed in the 12th century in the wake of the Crusades, many Jews devoted themselves to astrology. New christians, on the other hand, some influenced by their ancestors, while others in response to their difficult history and resistance to the dogmas of catholicism, continued these mystical and esoteric practices developed in the Iberian Peninsula. The inquisitorial process No. 7544 of Torre do Tombo, belonging to the astrologer and new christian Manuel Rodrigues, revives even more these hypotheses and affirmations about the role that new christians had in the expansion of mystical and esoteric practices, especially in Portugal. Based on a specific case, this work analyzes the importance of astrology in Portugal, in the 16th century, as well as the reasons of popular demands in seeking astrological consultations with the defendant. The space-time cut specifically covers the territory of Lisbon in the years 1583 and 1584. Accused of practicing judicial astrology and having books prohibited by the Tridentine Council, Manuel Rodrigues, was arrested when the inquisitorial censorship increasingly stiffened its rules and enlarged its catalogs with works considered heretical and forbidden. For almost a year of his lawsuit, the defendant got to scandalize the inquisitors with his confessions about his astrological practices and beliefs, and the heretical content of the works in his possession, including paintings, considered “dishonest”, that were seized at his residence. Starting from the perspective of the indiciary method and micro-history, this text tries to detect the particularities and experiences of this agent, whose worldview was the subject of persecution by the Portuguese Inquisition. Therefore, the focus here is to start from the reduction of scale and analyze the trajectory of this individual, the meaning and the sense that he attributed to astrology, his daily life and his strategies used to minimize the impact of the retaliations of an institution marked by intolerance and by social stigmas.